Consumer attitude of 'Y' generation towards mobile advertising in Kuala Lumpur, Malaysia. (11th June 2021) - Ganesh, R.; Fattakhova, Lolita
In the age of information communication technology, there is a penetrating rate of mobile commerce interactivity and consumer reliance on faster and efficient information search for buying decision. This study conceptualises and tests a theoretical framework of consumer attitude towards mobile advertising, which mainly investigates the influence of entertainment, informativeness, irritation, and personalisation towards consumer attitude in engaging mobile advertising with the 'Y' generation in Malaysia. The model proposes that perception of positive or negative in entertainment, informativeness, irritation, and personalisation towards the advertising message received through mobile phone, on how it affects the consumer attitude. The target respondents consist of 298 Malaysian 'Y' generation, and the model was tested with Pearson's correlation, standard multiple regression, and partial correlation. The finding reveals significant relationships between entertainment and informativeness with consumer attitude, but irritation was found not significant for regression. Notably, the personalisation variable reveals as a moderator with entertainment, informativeness, irritation towards consumer attitude. Thus, this study accentuates the importance of entertainment, informativeness, and personalisation towards positive consumer attitude formation with mobile advertising, which can effectively capture Generation Y consumer purchase intention, leading to purchase decision on a particular brand.